Virtual Tour As A Tourist Attraction Promotion Media Using Multimedia Development Life Cycle - Dwi Intan Af’idah (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This study is dedicated to the development of a comprehensive web-based virtual tour application known as the